The Effect of Promotion Costs and Production Costs on Net Sales (Case Study at PT. Unilever Indonesia, Tbk. Period 2016-2023) - Flora Oktayovie Nuzulul Ramadhina (Pusat Riset dan Inovasi Nasional, 2026)
PT Unilever Indonesia, Tbk. is one of the largest and most established Fast-Moving Consumer Goods (FMCG) companies in the world, having operated in Indonesia for decades. With an extensive product portfolio ranging from household essentials to personal care products, the company holds significant appeal for researchers looking to analyze its financial performance. The research title is “The Effect of Promotion Costs and Production Costs on Net Sales: A Case Study at PT Unilever Indonesia, Tbk. for the Period 2016–2023.” The research method applied in this study is quantitative descriptive. This approach was chosen to provide a systematic overview of the relationships between variables through statistical data. The primary data source for this study is secondary data, which includes details on promotion costs, production costs, and net sales figures for PT Unilever Indonesia, Tbk. over an eight-year period, from 2016 to 2023. All data was collected reliably from the annual reports officially published by the company on its website, www.unilever.co.id. In analyzing this information, the researcher used descriptive analysis to provide a summary of the data distribution. Furthermore, the data analysis technique employed was multiple linear regression. This technique was applied to accurately measure the extent of the influence of promotional costs and production costs, both partially and simultaneously, on the company’s net sales volume. Through this study, it is hoped that the cost-efficiency strategies implemented by management to maintain profitability growth amid increasingly competitive market conditions will be revealed.